The influence of feedback of diagnosis and executive function skills on rates of false positive and false negative outcomes for ADHD. Issue 2 (2nd April 2016) - Bender, Stacy L.; Privitera, Gregory J.
Abstract : This study examined executive function (EF) skills and self-reported symptoms of ADHD. EF skills were measured to determine whether skills were different between groups that reported clinical levels of ADHD symptoms (clinical group) and nonclinical levels of ADHD symptoms (nonclinical group). EF skills in the nonclinical group were also investigated to determine whether differences existed for those who received false positive and negative feedback about an ADHD diagnosis. Results indicated statistically and clinically significant differences in EF skills between the clinical and nonclinical group. Participants in the nonclinical group who reported elevated scores on the ADHD screener after receiving false positive feedback had statistically significantly different EF function scores, but not clinically significant scores, compared to the participants in nonclinical group who received negative feedback.